Pengaruh Social Media Marketing Instagram dan Kualitas Produk Terhadap Minat Beli Batik Iskandartex di Solo Raya - Amanda Putri Apriliani; Budi Istiyanto (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study examines the influence of Instagram-based social media marketing and product quality on consumer purchase intention of Batik Iskandartex in Solo Raya. A quantitative approach was applied using a Likert-scale questionnaire distributed to 96 respondents selected through purposive sampling. Multiple regression analysis reveals that both independent variables have a positive and significant impact on purchase intention. Visual content strategies, interactive communication, and consistent digital messaging effectively enhance consumer interest. Furthermore, perceptions of product durability, reliability, and aesthetics strengthen consumers’ intention to buy. These findings highlight the importance of integrating digital promotion with product quality enhancement to improve marketing effectiveness within the modern batik industry. The study contributes empirical insights for creative industry practitioners in designing marketing strategies aligned with digital consumer behavior.